Opportunities to Develop Students' Professional Competencies Based on the Integration of Disciplines - Elmurod Olloberdi o‘g‘li Ismoilov; Abdiqahhar Egamovich Tangirov (International Journal on Integrated Education, 2022)
This article analyzes the opportunities for the development of students' professional competencies based on the integration of disciplines and explains the importance of the integration of disciplines in the development of the education system. How to use the integration of sciences is explained in the example of teaching the topic "Approximate and numerical solution of differential equations." In addition, the article provides a number of methodological recommendations for teachers on the use of science integration.